A Randomized, Double-Blinded, Clinical Trial on Effects of a Vitis vinifera Extract on Cognitive Function in Healthy Older Adults - Calapai, Gioacchino; Bonina, Francesco; Bonina, Andrea; Rizza, Luisa; Mannucci, Carmen; Arcoraci, Vincenzo; Laganà, Germana; Alibrandi, Angela; Pollicino, Concetta; Inferrera, Santi; Alecci, Umberto (Frontiers in Pharmacology, 2017)
Introduction: Gradual population aging is creating a new set of needs in the general population. Memory capacity decreases with age, and memory deficits are considered an early symptom of Alzheimer’s Disease (AD), one of the most prevalent cognitive disorders in older people. Numerous studies have shown that grape polyphenolic compounds (GPs) are able to attenuate cognitive impairment and reduce brain lesions in experimental AD animal models. These GP effects are associated with improvement in brain antioxidant status and prevention of free radical-induced neuronal damage. We designed a randomized, double-blind, placebo-controlled clinical trial to investigate the potential beneficial effects of a Vitis vinifera-based dietary supplement on cognitive function and neuropsychological status in healthy older adults. Methods: One-hundred eleven subjects were recruited and randomly divided in two groups: one group received the V. vinifera-based dietary supplement Cognigrape® for 12 weeks (250 mg/day) and the second group received placebo over the same period of time. Before and after the end of the supplementation period, cognitive function and neuropsychological status were evaluated using the Mini-Mental State Examination (MMSE), Beck Depression Inventory (BDI), Hamilton Anxiety Rating Scale (HARS), and Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) evaluations. Results: MMSE scores were significantly improved after supplementation with Cognigrape® in comparison with baseline levels (p < 0.0001) and placebo (r = 0.59, 0.95% CI 0.11, 1.22; p < 0.0001). Cognigrape® supplementation produced a significant reduction in BDI (-15.8%) and HARS (-24.9%) scores with respect to baseline levels (p < 0.0001) and placebo (p < 0.0001 for BDI and p < 0.05 for HARS). RBANS total score was significantly improved by Cognigrape® with respect to baseline levels and placebo (r = 0.55, 0.95% CI 0.48, 6.07; p < 0.0001). The comparison with the placebo revealed improvements in several parameters among participants receiving Cognigrape®: attention (p < 0.001); language (p < 0.05); immediate memory (p < 0.0001); and delayed memory (p < 0.0001). Visuospatial/constructional abilities were not modified. During the study, no adverse effects were detected. Conclusion: The results show that 12 weeks of Cognigrape® supplementation is safe, can improve physiological cognitive profiles, and can concurrently ameliorate negative neuropsychological status in healthy older adults.